Strengthening rapid assessments in urban areas: lessons from Bangladesh and Tanzania - Garrett, James L.; Downen, Jeanne (Informa UK Limited, 2002)
The diversity of urban areas presents substantial challenges to the validity of information from rapid assessments, yet CARE s experiences in Bangladesh and Tanzania suggest a number of ways that rapid assessment procedures can be strengthened to address these concerns.